Ciliatasecones A–C, three rearranged limonoids from Toona ciliata var. yunnanensis. Issue 3 (21st December 2018) - Zhang, Pan-Pan; Cui, Zhi-Rong; Li, Yi; Heng, Li; Wei, Shan-Shan; Wang, Xiao-Bing; Yang, Ming-Hua; Luo, Jun; Kong, Ling-Yi
Abstract : Three rearranged limonoids with a novel ring- seco model and an unprecedented cycle system were isolated from Toona ciliata var. yunnanensis. Abstract : Ciliatasecones A–C (1–3 ), three rearranged limonoids with a novel ring- seco model and an unprecedented cycle system, were isolated from the root bark of Toona ciliata var. yunnanensis . Ciliatasecones A–B (1–2 ) share a novel cyclopenta[ b ]furan ring C/D system through C-9/11- seco and C-11/14 ether linkage. Ciliatasecone C (3 ) was found to possess a rare rearranged six-membered lactone ring B between C-7 and C-9. Plausible biogenetic pathway speculation indicated that C-9/11 cleavage and oxygen bridge formation played the key roles in the framework rearrangement of1–3 .